Impacts of temperature and pH on the distribution of archaeal lipids in Yunnan hot springs, China - Wu, Weiyan; Zhang, Chuanlun; Wang, Huanye; He, Liu; Li, Wenjun; Dong, Hailiang (Frontiers in Microbiology, 2013)
In culture experiments and many low temperature environments, the distribution of isoprenoid glycerol dialkyl glycerol tetraethers (GDGTs) commonly shows a strong correlation with temperature; however, this is often not the case in hot springs. We studied 26 hot springs in Yunnan, China, in order to determine whether temperature or other factors control the distribution of GDGTs in these environments. The hot springs ranged in temperature from 39°C to 94°C, and in pH from 2.35 to 9.11. Water chemistry including nitrogen-, sulfur- and iron species was also determined. Lipids from the samples were analyzed using LC-MS (liquid chromatography-mass spectrometry). Distributions of GDGTs in these hot springs were examined using cluster analysis, which resulted in two major groups. Group 1 was characterized by the lack of dominance of any individual GDGTs, while Group 2 was defined by the dominance of GDGT-0 or thaumarchaeol. Temperature was the main control on GDGT distribution in Group 1, whereas pH played an important role in the distribution of GDGTs in Group 2. However, no correlations were found between the distribution of GDGTs and any of the nitrogen-, sulfur- or iron species. Results of this study indicate the predominance of temperature or pH control on archaeal lipid distribution, which can be better evaluated in the context of lipid classification.